Economic and Social Conditions of Palestinian Refugee Camps Residents: Proposed Solutions (Balata Camp Model) - Arwa Hamdi Mahmmoud Jabali (My University, 2009)
This study examines one of the most important contemporary Palestinian issues, i.e. the socio-economic conditions of the residents of refugee camps in the West Bank. Balata Refugee Camp, near Nablus, serves as a practical model to identify the impacts of economic and social changes on its residents’ views and orientations in an attempt to develop future solutions for their status quo. To analyze the data, the study makes use of descriptive analytical methods based on (SPSS), geographic information systems (GIS), the next generation (Arc view GIS 3.3) and the Paint program for the Arabization of the maps. The researcher concludes that: A- The views of refugees and their attitudes toward the proposed solutions to their cause were as follows: 1 - (60.05%) of them do not accept to return without compensation; but if given the opportunity they will return although their economic and social obligations will not determine their decision to return.( 80.15%) of the refugees believe that the principle of return and establishing a Palestinian state will not be achieved merely through the return of 1948 refugees to the territory of the Palestinian Authority (West Bank and the Gaza Strip). 2- (87.2%) do not accept compensation without return and those who refuse to be compensated for material loss only are (83.2%). The majority of the refugees (96.5 %) reject the idea of settling down in the settlements instead of their own homes and properties in 1948. 3- (83.67%) reject the integratation and (staying or leaving the camp) solution with the knowledge that if they have the financial resources they prefer to leave the camp especially because it does not affect their faith in the right of return. Therefore, the just solution to the refugee problem is return and compensation. B- The study also finds that there is no impact of gender, age, educational level and number of family members on the views of refugees and their attitudes toward the proposed solutions. C- The income variable affects the total score of the refugee views and tendencies towards the proposed solution of their status quo in the camps for the sake of those with low income (900 ILS per month) over those with high income (2501-3000 begin_of_the_skype_highlightingend_of_the_skype_highlighting ILS per month). Refugees with low income (900 ILS) have more positive attitudes towards the proposed solutions than those who have high levels of income(2501-3000)begin_of_the_skype_highlightingend_of_the_skype_highlighting ILS per month). D- Finally, the study concludes that the occupation variable affects the refugees’ attitudes towards the proposed solutions. Workers in the private sectors have more positive attitudes towards the (right of return) and/or (staying in or leaving the camp) than those who work in the public sector mainly those who work for UNRWA due to their high level of stability which the public sector workers lack. E- The researcher recommends the necessity of providing appropriate shelters for the refugees until their problem is solved.

تعالج هذه الدراسة قضية من أهم القضايا الفلسطينية المعاصرة، وهي الكشف عن الواقع الاقتصادي والاجتماعي لسكان المخيمات الفلسطينية في الضفة الغربية، باتخاذها مخيم بلاطة نموذجاً تطبيقياً للتعرف على مدى تأثير المتغيرات الاقتصادية والاجتماعية على آراء سكانه وتوجهاتهم محاولةً وضع حلول مستقبلية لوضعهم الحالي . وقد استخدمت الدراسة المنهج الوصفي التحليلي معتمدة على برنامج ( ٍSPPS) لتحليل البيانات، وبرنامج نظم المعلومات الجغرافية (GIS) وذلك باستخدام الجيل (Arc veiw gis 3.3) وبرنامج الرسام لتعريب الخرائط. وقد خلصت الدراسة إلى الآتي: أ‌- أنّ آراء اللاجئين وتوجهاتهم نحو الحلول المقترحة لقضيتهم كانت على النحو الآتي: 1- انَّ منهم من لا يقبلون بالعودة دون التعويض وذلك بنسبة (60.05%) ، لكن لو أتيحت لهم الفرصة سيعودون مع العلم أن ارتباطاتهم الاقتصادية والاجتماعية لن تؤثر على قرارهم بالعودة ، وتبين أن(80.15%) يرون أن مبدأ العودة وإقامة دولة فلسطينية لا يتحقق بعودة لاجئي عام 1948م فقط إلى أراضي السلطة الفلسطينية( الضفة الغربية وقطاع غزة). 2-ومنهم من لا يقبلون بالتعويض دون العودة وذلك بنسبة ( 87.2%) وقد بلغت نسبة من يرفضون التعويض فقط عن الأضرار المادية(83.2%) ، كما تبين أن الأغلبية يرفضون فكرة التعويض بالسكن في إحدى المستعمرات بدلاً عن بيوتهم وممتلكاتهم التي خسروها عام 1948م وذلك بنسبة ( 96.5%). 3-و تبين أن (83.67%) يرفضون حل (الاندماج) و(البقاء أو الخروج من المخيم) مع العلم أنه إذا توافرت لديهم الإمكانيات المادية فإنهم يفضلون الخروج من المخيم، مع العلم أنه لا يؤثر على إيمانهم بحق العودة، ويعتبرون وجود المخيم وبقاءه صامداً دليلاً على حقهم بالعودة. إذن فالحل العادل لقضية اللاجئين هو العودة والتعويض. ب‌- وخلصت الدراسة أيضاً إلى أنه لا يوجد تأثير لكل من متغير الجنس والعمر والمستوى التعليمي وعدد أفراد الأسرة على آراء اللاجئين وتوجهاتهم نحو الحلول المقترحة. ج- وخلصت كذلك إلى أن هناك تأثيراً لمتغير الدخل في الدرجة الكلية على آراء سكان مخيم بلاطة وتوجهاتهم لرسم الحلول المستقبلية لوضعهم الحالي في المخيم، فاتضحت الفروق بين مستويات ذوي الدخل الأقل من( 900 شيكل) من جهة ومستويات ذوي الدخل (2501-3000 شيكل ) من جهة أخرى لصالح من دخلهم أقل من(900 شيكل)، بمعنى أن اللاجئين الذين مستوى دخلهم (أقل من 900 شيكل) لديهم اتجاهات أكثر ايجابية نحو الحلول المقترحة لوضعهم الحالي من الذين مستوى دخلهم(2501-3000 شيكل). د- وخلصت أخيرًا إلى أنه ثم تأثير لمتغير الوظيفة على آراء سكان مخيم بلاطة وتوجهاتهم لرسم الحلول المستقبلية لوضعهم الحالي في المخيم، حيث كانت اتجاهات الأفراد الذين يعملون في القطاع الخاص نحو حل (العودة) و (البقاء أو الخروج من المخيم) و (الدرجة الكلية) أكبر من اتجاهات موظفي وكالة الغوث ( الأونروا)، ويعود السبب في ذلك لكون وضع من يعمل لدى وكالة الغوث أكثر استقراراً ممن يعمل في القطاع الخاص. هـ - وأوصت الدراسة بضرورة توفير السكن اللائق لأهالي المخيم إلى حين حل قضيتهم مستقبلا.
الأوضاع الاقتصادية والاجتماعية لسكان المخيمات الفلسطينية، الحلول المقترحة: مخيم بلاطة نموذجاً